Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan: (Studi Pada Pt. Aneka Tambang Tbk Periode 2021, 2022, Dan 2023) - Bagus Bimma Priyambada; Diah Ayuning Novianti; Nicko Albart (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the company’s financial performance using financial ratio analysis. The financial ratios employed include liquidity ratio, solvency ratio, and activity ratio. The data source used in this research is secondary data, namely the financial statements of PT Aneka Tambang Tbk from 2021 to 2023. The data collection technique used is documentation. The analytical method applied is the time series analysis method, which compares the company’s financial performance over several periods. The results of the liquidity ratio analysis indicate that the company is in a good condition, although the ratio increased due to a decrease in current liabilities. The results of the solvency ratio analysis show that the company is in a favorable condition, as the debt ratio and debt-to-equity ratio have increased each year. This increase in solvency ratios occurred because total liabilities continued to rise, implying that the company’s assets and equity are still financed by debt. The results of the profitability ratio analysis show an upward trend from year to year. The average return on equity of PT Aneka Tambang (Persero) Tbk over the past three years is 12.08%. This increase was driven by a significant rise in total equity compared to the previous year. Thus, it can be concluded that the company is in a good condition as it is able to generate optimal profits. The results of the activity ratio analysis also indicate an increase each year, suggesting that the company is efficient and effective in utilizing all of its assets.